Impact of urban block shape on traffic and air quality: A SUMO-based comparative study of rectangular, radial, and triangular forms - Ismail Essamlali; Hasna Nhaila; Mohamed El Khaili (Transportation Research Interdisciplinary Perspectives)
Urban transportation emissions significantly contribute to air quality degradation in cities. Traffic patterns and air quality are known to be interconnected, highlighting the critical role of urban form in influencing both. This study employs Simulation of Urban Mobility (SUMO), a traffic simulation software to investigate how urban block form (rectangular, radial and triangular) affects traffic flow and potential air pollution. We analyze three cities (Barcelona, Paris and Curitiba) representing each block shape. The results indicate that rectangular block layouts, as exemplified by Barcelona, promote optimal traffic flow and potentially lower emissions. Conversely, triangular block configurations exhibit the least favorable performance. These findings emphasize the importance of urban form, particularly block shape, as a tool for managing traffic flow and potentially improving air quality in cities.